Professional and creative path of architect Pavel Pavlovich Golyshev - N. V. Algazina (Омский научный вестник: Серия "Общество. История. Современность")
In the article there are systematizes and specified biographical facts of P. P. Golyshev — the Russian military engineer, architect and educationalist. The author’s architectural objects of P. P. Golyshev built in Kazan and Omsk are presented. The purpose of this article is to provide the most complete information about the professional and creative biography of P. P. Golyshev. The novelty of the research consists in the systematization of reference material, biographical information and the periodization of the professional, pedagogical and practical activities of P. P. Golyshev as an engineer-architect